Impact of Strategic Audit on Enhancing the Efficiency of the Internal Control System: A Study of Industrial Companies in Iraq - Muhammad Ali Jaafar; Alaa Mohsin Muttlaq Al-Daamy (Technium Social Sciences Journal, 2024)
The study aims to provide a general and brief introduction to the audit process, demonstrate traditional and modern performance measurement tools and methods that are compatible with strategic auditing, and provide a conceptual framework for strategic auditing and the internal control system. And the relationship between them. It helps the concerned establishments increase their performance and achieve their goals in light of the results of the study. The research sample consisted of the General Company for Textile Industries in Iraq, which is the Baghdad Laboratory, the Nineveh Laboratory, the Diwaniyah Laboratory, and the Babylon Laboratory (according to the SPSS statistical program). The purpose of the study was to know the extent to which industrial companies in Iraq apply strategic audit mechanisms, what their impact is on the internal control system in companies, and how to benefit from the application of these strategies in the audit process. The study found a relationship between the efficiency and effectiveness of strategic auditing and improving the efficiency of the internal control system. Increasing the efficiency of the internal control system using the strategic audit method. The study recommended implementing the strategic review system effectively to benefit from its advantages in increasing the efficiency of the internal control system in companies in general and industrial companies in particular and trying to use advanced techniques to measure the internal control system.